Genome sequences of two cold-adaptedCryobacterium spp. SO1 and SO2 from FildesPeninsula, Antarctica - C. P. Teoh; Clemente Michael Vui Ling Wong; D. J. H. Lee; M. A. González; N. Najimudin; P. C. Lee; Y. K. Cheah (2018)
Psychrophilic and psychrotrophic bacteria play important roles in nutrient cycling in cold environments. These bacteria are suitable as model organisms for studying cold-adaptation, and sources of cold-active enzymes and metabolites for industrial applications. Here, we report the genome sequences of two Cryobacterium sp. strains SO1 and SO2. Genes coding major proteins related to cold- or thermal-stress adaptations and those with industrial applications found in their genomes are described.